Assessing the impact of five teaching strategies on the academic performance of senior high school students in financial accounting: A case study in Wa - Mahasus Abubakari Kassim; Samuel Marfo; Karim Abu (Social Sciences and Humanities Open)
This study compared the effects of case studies, group projects, role-playing, technology integration, and cooperative learning strategies on the academic performance of Senior High School students in Financial Accounting in Wa, Upper West Region of Ghana. The research was motivated by the persistently low academic performance of students in Financial Accounting in the region. Five research questions and one hypothesis were formulated and tested at a 0.05 significance level. A quasi-experimental design was adopted, incorporating pre-tests, post-tests, and control groups. Over three weeks, lesson plans employing case studies, group projects, role-playing, technology integration, and cooperative learning strategies were implemented in the experimental group, while the control group received traditional instruction. The study was grounded in Social Constructivist Learning Theory and Situated Learning Theory. The study population comprised 324 Financial Accounting students from three Senior High Schools. Using Yamane's sample size determination formula and a simple random sampling method, 200 participants were initially recruited to account for potential attrition. A total of 190 participants completed the study, ensuring the representativeness and validity of the findings. The research instruments included the Financial Accounting Achievement Test (reliability coefficient of 0.77, assessed using the Kuder-Richardson Formula 20) and the Financial Accounting Teaching Toolkit. Analysis of Variance (ANOVA) was used to test the hypothesis. The findings revealed that case studies, role-playing, technology integration, and cooperative learning significantly improved students' academic performance in Financial Accounting. Based on these results, it is recommended that teachers and educational institutions prioritize these strategies in Financial Accounting instruction. Professional development workshops and ongoing training programs should focus on equipping teachers with the tools and techniques for effective implementation.